Older Black Adults' Satisfaction and Anxiety Levels After Completing Alternative Versus Traditional Cognitive Batteries. - Gamaldo, Alyssa A; Tan, Shyuan Ching; Sardina, Angie L; Henzi, Carolyn; Guest, Rosalyn; Ross, Lesley A; Willingham, Kurtis; Zonderman, Alan B; Andel, Ross A (Journals of Gerontology Series B: Psychological Sciences & Social Sciences, 2020)
Objective The objective of this study was to examine satisfaction, test anxiety, and performance using computer-based cognitive batteries versus a paper-and-pencil neuropsychological battery among older Blacks. Method Self-identified Black adults (n = 87, age range: 55–86; mean education = 14) completed two computer-based tests (CogState and Joggle) and a paper-and-pencil neuropsychological battery. After each battery, participants reported their testing anxiety and satisfaction using the batteries. Descriptive, correlational, and regression analyses compared satisfaction, anxiety, and performance across the batteries. Results Majority of the participants reported more satisfaction with the computer-based (Joggle: 66%; CogState: 77%) than the neuropsychological (52%) battery. Participants also reported less testing anxiety after completing the computer-based batteries than the neuropsychological battery, F (2, 172) = 22.96, p <.001. Older adults' familiarity and comfort level with the computer were not associated with their performance on the computer-based tests (p >.05). Although testing anxiety was not associated with performance across the batteries, age and education quality were uniquely associated with performance on the CogState and neuropsychological batteries. Conclusions Computer-based cognitive batteries appear to be less intimidating than the commonly used paper-and-pencil neuropsychological tests for Black adults. Thus, these cognitive batteries may be useful tools for monitoring older Blacks' cognitive status.